Breaking the cycle: localising humanitarian aid in Ukraine - Noe, N; Lang, H (Refugee Studies Centre, University of Oxford, 2023)
Localising the humanitarian response in Ukraine would improve the sustainability and reach of the overall response – and set a valuable precedent.  Addressing barriers to localisation and Ukrainians demanding reform are key.